Technical aspects of EVAR for infrarenal AAA - Hyhlik-Dürr, Alexander; Bischoff, Moritz; Hakimi, Maani; Tengg-Kobligk, Hendrik von; Böckler, Dittmar (The journal of cardiovascular surgery, 2012)
Technical aspects are crucial for planning and performing successful endovascular repair of abdominal aortic aneurysms (AAA). Planning should be based on high-quality computed tomography angiography scans with a slice thickness of ≤ 1 mm. However, even without a workstation for image postprocessing, important angle estimations can be easily performed. Several devices are available today to treat abdominal aneurysms. In most elective cases all currently available 3rd generation devices perform comparably if minimal requirements are kept in mind. A safe and technically precise implantation requires cooperation with the involved anesthesiologist in order to manage anticoagulation, blood pressure regulation in general and in currently evolving regional anesthesia. Modern endograft implantation involves highly technical resources, for example guide wires or catheters. Beside patient selection, an optimal procedure planning, graft model choice and endovascular skills are mandatory aspects. In the near future, further improvements in device design and deployment mechanism will allow better device alignment, paving the way for an even broader application of endovascular aneurysm repair (EVAR).